Análise da produção de biogás em diferentes sistemas e fases de criação de suínos no oeste do Paraná - Grosbelli, Andressa Carla (2018)
Besides the concern with the exhaustion of energy sources and environmental consequences, it is necessary to know the potential that these sources of energy (swine manure) can present. The present work has had the objective of discussing and analyzing, on the basis of field and laboratory studies, the production of biogas in different breeding types and stages of pigs, being the treatments: two nursery units (T1 and T2), three growth and termination units (T3, T4 and T5) and two piglets production units (T6 and T7). ST and SV analyzes were performed, reducing the organic load of the swine manure used. The biodigestors used were batch type, made of PVC pipes and fed with the waste from different types of pig farming. The HRT was 45 days and significant averages of biogas production, ST and SV removal were found, good volume yield related to SVs removed and added. The T5 treatment presented the best removal of COD (72.3%), being also the one that produced the most biogas during the 45 days (5.3L), nevertheless it presented a low efficiency in the removal of the volatile solids, being necessary a time of HRT higher for better treatment efficiency. On the other hand, the T7 treatment presented the best values of removal efficiency of volatile solids during the study period, with 71.48%